2016
DOI: 10.3390/met6110266
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Assessment of Impending Fracture in a Cyclically Loading Structural Steel

Abstract: Using the advanced acoustic emission (AE) technique, we address the problem of early identification of crack initiation and growth in ductile structural steels under cyclic loading. The notched 9MnSi5 steel specimens with weld joints were fatigue tested at room and lower temperatures with concurrent AE measurements. Detection of AE in ductile materials where fatigue crack initiation and propagation is mediated by local dislocation behavior ahead of the notch or crack tip is challenging because of an extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In a study, Shankhwar et al [128] used a trilinear interpolation method, an interactive Mixed Reality (MR)-based user interface, a Gradient Boosted Regression Tree (GBRT) model, and FEA to visualize the results of hand metal arc welding. In a cyclically loaded structural steel, the Acoustic Emission (AE) examination of proximate fracture was carried out by Rastegaev et al [129] using AE data. A combination of criteria based on power spectrum and pattern recognition, as well as energy data and spectral density functions was used.…”
Section: Random/hybrid Based Methodsmentioning
confidence: 99%
“…In a study, Shankhwar et al [128] used a trilinear interpolation method, an interactive Mixed Reality (MR)-based user interface, a Gradient Boosted Regression Tree (GBRT) model, and FEA to visualize the results of hand metal arc welding. In a cyclically loaded structural steel, the Acoustic Emission (AE) examination of proximate fracture was carried out by Rastegaev et al [129] using AE data. A combination of criteria based on power spectrum and pattern recognition, as well as energy data and spectral density functions was used.…”
Section: Random/hybrid Based Methodsmentioning
confidence: 99%
“…An analysis of the existing methods and means for determining the degradation of the mechanical properties of materials during the operation of structures in real time showed that they are all intended for the study of one type of deformation: tension [ 37 , 38 , 39 ] or bending [ 40 , 41 , 42 , 43 ], while under real conditions loading forces act on the material, under combined conditions of deformation [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Relative Workmentioning
confidence: 99%
“…Due to its sensitivity to microstructure parameters, the AE method of application makes it possible to detect violations of the structural composition in the material [17][18][19]. In a number of experimental research studies [20][21][22][23][24][25], it was found that the AE method If such dissimilar welded joints are operated for a long time at high temperatures, the diffusion processes will proceed intensively, and as a result the interlayers will increase in size. The presence of such interlayers negatively affects the mechanical properties of the welded joint [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its sensitivity to microstructure parameters, the AE method of application makes it possible to detect violations of the structural composition in the material [17][18][19]. In a number of experimental research studies [20][21][22][23][24][25], it was found that the AE method can be effectively applied to detect defects in welded joints, as well as to identify and locate them.…”
Section: Introductionmentioning
confidence: 99%